Sustaining good health through the consumption of cosmos candatus Ulam Raja from KENMS vegetable garden - Mhd. Sarif, Suhaimi; Zainudin, Dolhadi (2019)
This study explains the experience in the consumption of cosmos candatus kunth (Ulam Raja) planted at the SDG IIUM KENMS vegetable garden. The project was started in April 2019 and officiated by Honourable Rector in August 2019. After a few times consuming ulam raja as part of lunch meals, a few colleagues have experienced some benefit. They felt easy digestion and produced gassy after lunch meals. In addition, they could save some money to purchase ulam raja salad. December 2019 will the last month to consume ulam raja as the plant has reached maturity stage. All the seeds are harvested for the next round of planting.